The use of supplementary materials in EFL classes: A comparative analysis of public and private high schools - Tobar Ojeda, Alba del Consuelo (2012)
This study explores the use of supplementary materials in EFL Classes. The purpose of this study was to determine which were the most frequent supplementary materials used by teachers. Qualitative and quantitative methodologies were used in order to ensure the best results. The Literature review was based on a wide-range of text references; classes were structurally observed and data was collected in the observation matrixes. Moreover, surveys were administered to students and English teachers. Two high Schools, one public and one private were chosen randomly to do the research in the north of the city of Quito, Ecuador. The sample was a group of students from first, second, and third year as well as their teachers. As conclusion, it may be said that both schools used supplementary material. In private school, supplementary materials were used slightly more often than in public education. Visual aids rated as most commonly used in both schools since teachers do not realize the importance of use different supporting materials. The use of supplementary material increases the comprehension of EFL among students with different learning styles.